Compensation of Physical Activity and Sedentary Time in Primary School Children - RIDGERS, NICOLA D. (Lippincott Williams & Wilkins, 2014)
PURPOSE: There is considerable debate about the possibility of physical activity compensation. This study examined whether increased levels in physical activity and/or sedentary behavior on 1 d were predictive of lower levels in these behaviors on the following day (compensatory mechanisms) among children. METHODS: Two hundred and forty-eight children (121 boys and 127 girls) age 8–11 yr from nine primary schools in Melbourne, Australia, wore a GT3X+ ActiGraph for seven consecutive days. Time spent in light physical activity (LPA) and moderate- to vigorous-intensity physical activity (MVPA) was derived using age-specific cut points. Sedentary time was defined as 100 counts per minute. Meteorological data (temperature, precipitation, relative humidity, and daylight hours) were obtained daily and matched to accelerometer wear days. Multilevel analyses (day, child, and school) were conducted using generalized linear latent and mixed models. RESULTS: On any given day, every additional 10 min spent in MVPA was associated with approximately 25 min less LPA and 5 min less MVPA the following day. Similarly, additional time spent in LPA on any given day was associated with less time in LPA and MVPA the next day. Time spent sedentary was associated with less sedentary time the following day. Adjusting for meteorological variables did not change observed compensation effects. No significant moderating effect of sex was observed. CONCLUSION: The results are consistent with the compensation hypothesis, whereby children appear to compensate their physical activity or sedentary time between days. Additional adjustment for meteorological variables did not change the observed associations. Further research is needed to examine what factors may explain apparent compensatory changes in children’s physical activity and sedentary time.